PENGARUH LAJU ALIRAN UDARA DAN LAMA FERMENTASI CAIRAN PULPA HASIL SAMPING FERMENTASI BIJI KAKAO TERHADAP KARAKTERISTIK CUKA FERMENTASI - Mega Suasti Rahayu, Ni Made; Ganda Putra, G.P.; Suwariani, Ni Putu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 5 No 2 (2017): April, 2017)
Vinegar fermentation is a liquid product which containing of acetic acid, and obtained from ingredients that containing of carbohydrate and alcohol. The aims of this study were to determine the effect of air flow rate and time of fermentation on the characteristics of vinegar fermentation from liquid waste of cocoa beans fermentation, and to determine the best treatment which can produces vinegar fermentation from liquid waste of cocoa beans fermentation. The experiments in this study using a Completely Randomized Design (CRD) with two factors. The first factor is the rate of air flow which consists of three levels: 0.50 vvm ?¹, 1.00 vvm ?¹, and 1.50 vvm ?¹. The second factor is time of fermentation that consists of four levels: 10, 15, 20 and 25 days. The results showed that the treatment of air flow rate and interaction of both treatments was affected significantly (P<0.01) on levels of acetic acid content, total sugar and pH levels, but did not effected (P>0.05) on the alcohol content and total suspended solid. Time of fermentation treatment, showed a significant effect (P <0.05) on level of acetic acid content, but did not effected (P>0.05) on the alcohol content and affected significantly (P<0.01) on sugar content, pH, and total suspended solid of vinegar fermentation from liquid waste of cocoa beans fermentation. The best treatment is by using air flow rate, amount 0.50 vvm ?? and fermentation for 25 days, which can produce vinegar fermentation from liquid waste of cocoa beans fermentation that containing 2.64 % (v/v) of acetic acid, 3.30 of pH, 4.30 ?brix of total suspended solid, 0.29 % (v/v) of total sugars and 0.00 % (v/v) of alcohol content. Key words: vinegar fermentation, the air flow rate, fermentation period